Physiological, molecular, and epigenetic aspects of early transient nitrogen deprivation recovery in maize - Hernández Pridybailo, Andrés 1988- (2024)
Maize is a widely cultivated crop and a primary food source for humans and livestock. Along with its substantial contribution to biomass for fuel production, maize is the most produced cereal globally. However, despite its prevalence, improving nitrogen (N) use efficiency in maize presents ongoing challenges. Understanding how maize plants utilize nitrogen is crucial for identifying traits that could aid breeders in addressing this efficiency gap. When plants experience transient stress and return to previous conditions, a recovery phase is initiated, acclimating the plants and potentially enhancing their responses to subsequent stress events. This mild or transient stress is termed "eustress," and its intentional manipulation is referred to as "crop priming." Crop priming, extensively studied in the context of drought, was explored in our previous research, which revealed that nitrogen supplementation during recovery from early transient water deficits enhances priming effects. This highlights the pivotal role of N in priming and that impaired N supply might negatively affect any acclimation to future stresses. Notably, there is limited literature on transient N deprivation, with most studies focusing on plant responses under conditions of maintained N deficiency. Furthermore, epigenetic regulation of plant mineral nutritional responses via DNA methylation has been reported, like many aspects of plant development that are regulated by such mechanism. Epigenetics is the study of phenotypic changes that can be inherited through mitosis or meiosis, which cannot be explained by changes in the DNA sequence. DNA methylation is the covalent modification of cytosines by the addition of a methyl group, which, depending on its location in the genome, can affect genomic stability and gene expression. Previous results have revealed that N deficiency modifies the methylome of maize roots, hypomethylating transposable elements in a nutrient-specific way...